Metode Pembelajaran dengan Bermain Peran dalam Pendidikan Triase untuk Mahasiswa Keperawatan - Leli Rezky Dwi Oktavia; Wiwik Kusumawati (Ilmiah Institut Citra Internasional, 2019)
The nursing profession requires scientific knowledge, technical abilities and skills. Choosing the right and best teaching method is the most important step in the education process. Role playing is a versatile activity that can facilitate students to learn in real situations. this is a teaching method that has strong and interesting potential to build the skills of nursing students in triage education. Research Objectives: To Provide information about the influence of role-playing method on triage education for nursing students. Method: Sources of research were taken from 3 databases namely PubMed, ProQuest and Ebsco and from Google Scholar using keywords